2012
DOI: 10.1177/0269215512444632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of a nine-month web-based intervention in subacute non-specific low back pain patients: a randomized controlled trial

Abstract: The intervention showed clinical improvements in quality of life and selected lower back pain outcomes in the experimental group compared to the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(107 citation statements)
references
References 27 publications
3
87
1
Order By: Relevance
“…These interventions should use social marketing to educate drivers on healthier sitting postures and strengthening, mobility and stretching exercises to help prevent and treat LBP. 38,39 It is necessary to communicate our findings and these recommendations to both policy makers and to the drivers themselves for early prevention and intervention for LBP.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These interventions should use social marketing to educate drivers on healthier sitting postures and strengthening, mobility and stretching exercises to help prevent and treat LBP. 38,39 It is necessary to communicate our findings and these recommendations to both policy makers and to the drivers themselves for early prevention and intervention for LBP.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In an initial report from this trial, we concluded that the intervention produced clinically important improvement in the health-related quality of life of patients with NLBP. 9 To extend this knowledge, the present report intends to provide further understanding of the effects of this intervention in 2 ways: first, by assessing the feasibility and safety of a 9-month intervention; second, by reporting magnitudes of improvements in trunk muscle endurance, functional disability, and recurrent episodes of LBP. This additional knowledge will allow researchers and clinicians to better characterize changes induced by this intervention, and to compare the magnitude of the effects to that of other therapeutic interventions to prevent work site-related LBP.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Understanding the cause of a back pain is essential with a specific end goal to expel it from the patient's life and not to duplicate the development amid treatment [35]. Nonetheless, when the reason for the back pain is obscure, endorsing focused on treatment can demonstrate predicaments, which then leads to general exercise being frequently suggested [36]. At most times, intercession programs have received a mono-disciplinary way to deal with restoring (NSCLBP) [15,21,25].…”
Section: Introductionmentioning
confidence: 99%